Pengaruh Sosio Budaya dalam Pemberian ASI Eksklusif dan MP-ASI Dini Dikaitkan dengan Status Gizi pada Anak Usia 6-23 Bulan di Wilayah Kerja Puskesmas Banyuanyar Kabupaten Sampang - Fadilah, Annisa Nur; Sumarmi, Sri (Universitas Airlangga, 2024)
Background: Problems with children's nutritional status can arise due to factors that are interconnected with others. The main factor that causes nutritional problems in children is the lack of knowledge of the importance of adequate nutritional intake for children. Based on data from the ePPGBM East Java 2021 Health Profile, toddlers in Sampang District are undernourished with 4,646 people, stunted toddlers with 2,425 people, and thin toddlers with 1,609 people. Objectives: Knowing the socio-cultural influence of exclusive breastfeeding and early complementary feeding on the nutritional status of children aged 6-23 months in the Banyuanyar Health Center working area, Sampang Regency. Methods: This research uses quantitative methods and uses cross sectional studies. The number of samples to be used in this study used 100 respondents of mothers with children aged 6-23 months. Sample selection using multistage random sampling technique. The data were tested using chi square, Fisher's Exact and logistic regression tests. Results: The results showed that there was no influence between socio-culture during pregnancy with exclusive breastfeeding (p = 0.000), postpartum socio-culture with exclusive breastfeeding (p = 0.226), socio-culture during breastfeeding with exclusive breastfeeding (p = 0.732). There was no association between socio-culture and early complementary feeding (p-value for honey=0.142, p-value for formula=0.185, p-value for banana=0.298, p-value for young coconut=0.135, p-value for tajin water=0.142, p-value for team rice=0.809, p-value for cornstarch=0.380, p-value for rice cake=0.135, p-value for instant porridge=0, 285, p-value of fruit puree=0.0.135, abstinence from too much sea fish=0.529), and there is no effect between exclusive breastfeeding on children's nutritional status (p-value of Weight-for-age index=0.182, p-value of Length for-age index=0.931, p-value of Weight-for-length index=0.717) and early complementary feeding on children's nutritional status (p-value of Weight-for-age index=0.482, p-value of Length for-age index=0.134, p-value of Weight-for-length index=0.541). Conclusions: The conclusion of this study is that there is no socio-cultural influence on exclusive breastfeeding and early complementary feeding on nutritional status in children aged 6-23 months in the Banyuanyar Health Center working area, Sampang Regency.